Clinicopathologic Significance of Intestinal-type Molecules' Expression and Different EGFR Gene Status in Pulmonary Adenocarcinoma. Issue 5 (May 2019) - Feng, Chang; Feng, Man; Gao, Yujun; Zhao, Xiaogang; Peng, Chuanliang; Yang, Xiangshan; Zhang, Jing
Abstract : Variant pulmonary adenocarcinoma with intestinal-type molecules shares similar molecular expression with colorectal carcinoma. However, expression of such molecules and their association with survival time with clinicopathologic parameters, such as epidermal growth factor receptor (EGFR) gene status in other types of pulmonary adenocarcinoma, has been rarely demonstrated. Sixty patients with resected pulmonary adenocarcinoma were divided into the enteric differentiation group (I group, n=30) and the usual group (U group, n=30). Immunohistochemical staining was used to assess the expression of carcinoembryonic antigen (CEA), Villin, CK20, and caudal-related homeobox 2 (CDX2). EGFR gene status was examined by Fluorescence Quantitative polymerase chain reaction. Kaplan-Meier survival curve was drawn by GraphPad Prism 5.0 software. The results showed that there was a significant difference between the 2 groups ( P <0.05) in the expression of Villin, CK20, and CDX2, whereas the expression of CEA showed no significant difference ( P >0.05). Compared with the U group, patients in the I group were mainly female individuals and in clinical stages III to IV, prone to lymph node metastasis ( P <0.05). The patients in the I group with CDX2 + CK20 − phenotype (tumor size>5 cm) had a shorter survival time ( P <0.05), and EGFR gene status was not associated with median survival time and the expression of CEA, Villin, CK20, and CDX2 ( P >0.05). Thus, our research indicates that patients with enteric differentiation have unique clinical characteristics and different prognosis, which may play important roles in diagnosis and choosing therapeutic strategies for pulmonary adenocarcinoma patients in clinical practice. Abstract : Supplemental Digital Content is available in the text.